2008
DOI: 10.1124/mol.107.041012
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Cross-Talk between Drug Metabolism and Lipid Homeostasis: Constitutive Androstane Receptor and Pregnane X Receptor Increase Insig-1 Expression

Abstract: Activation of pregnane X receptor (PXR) and constitutive androstane receptor (CAR) by xenobiotic inducers of cytochromes P450 is part of a pleiotropic response that includes liver hypertrophy, tumor promotion, effects on lipid homeostasis, and energy metabolism. Here, we describe an acute response to CAR and PXR activators that is associated with induction of Insig-1, a protein with antilipogenic properties. We first observed that activation of CAR and PXR in mouse liver results in activation of Insig-1 along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 34 publications
8
99
1
Order By: Relevance
“…Activation of CAR by the synthetic agonist TCPOBOP increased insulin sensitivity and ameliorated liver steatosis in both high fat diet (HFD)-and leptin deficiency-induced obesity [77,78] . Several studies have shown that pharmacological activation and the genetic gain-of-function of CAR leads to lower hepatic triglyceride levels, whereas loss of CAR causes basal accumulation of triglycerides in the liver [79] . The LXR-SREBP pathway plays a central role in hepatic lipogenesis by transducing the genes involved in fatty acid biosynthesis and lipid uptake [80] .…”
Section: Car In Energy Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of CAR by the synthetic agonist TCPOBOP increased insulin sensitivity and ameliorated liver steatosis in both high fat diet (HFD)-and leptin deficiency-induced obesity [77,78] . Several studies have shown that pharmacological activation and the genetic gain-of-function of CAR leads to lower hepatic triglyceride levels, whereas loss of CAR causes basal accumulation of triglycerides in the liver [79] . The LXR-SREBP pathway plays a central role in hepatic lipogenesis by transducing the genes involved in fatty acid biosynthesis and lipid uptake [80] .…”
Section: Car In Energy Metabolismmentioning
confidence: 99%
“…Insulin-induced gene-1 (Insig-1) is an endoplasmic reticulum-bound cholesterol sensor that suppresses the proteolytic activation of SREBPs when sterols are abundant [81] . CAR binds to the DR4 element on the Insig-1 promoter and directly induces the expression of Insig-1, therefore preventing SREBP1 from entering the nucleus to induce lipogenic genes [79] . Unlike Insig-1 that directly targets the activation of SREBP1, sulfotransferase 2B1b (Sult2B1b), another CAR responsive gene, inhibits Srebp1 expression and hepatic lipogenesis through enzymatic deactivation of LXR ligands.…”
Section: Car In Energy Metabolismmentioning
confidence: 99%
“…CAR and PXR have been also shown to modulate the immune response and the genes involved in lipid and cholesterol synthesis (Moreau et al, 2007;Roth et al, 2008). No definite physical ligand have been identified for both CAR and PXR, but previous reports show they exhibit the ability to bind multiple ligands (Tzameli et al, 2000;Sueyoshi and Negishi, 2001;Willson and Kliewer, 2002;Maglich et al, 2003).…”
Section: Arpiainen Et Al (2005) Identified a Putative Ahr Response Ementioning
confidence: 99%
“…In the former, PXR activates CD36 to increase free fatty acid uptake and hepatic lipid accumulation ( 21 ). With regard to SREBP-dependent lipogenic pathways, PXR can induce Insig-1 via a functional binding site in the Insig-1 promoter, resulting in decreased levels of active SREBP-1 and reduced triglyceride synthesis ( 22 ). Although these studies showed opposite effects of PXR activation on lipid homeostasis, the overall fi ndings are consistent with a role for PXR in mediating lipid homeostasis at multiple levels.…”
Section: Superarray Analysismentioning
confidence: 99%